The Development of Working Memory Abilities of Early Childhood Children with Learning Activities According to The Principle of Iddhipada: The Development of Working Memory Abilities of Early Childhood Children with Learning Activities According to The Principle of Iddhipada - Anupan, Pongsakorn; Aphipanyo, Phrapalad Soravit; Wormoklalo, Phrakhrupalad Maroot (RATANABUTH JOURNAL, 2023)
The purpose of this research was to develop working memory of preschool children through learning activities based on Iddhipad 4 education and to compare for preschool children. before and after educational game activities The sample consisted of 25 male and female early childhood children, aged 3-4 years old, studying in kindergarten 1, semester 1, academic year 2022, of Wiang Theung Sub-district Municipal School. was obtained by selective selection method. The research tool was an activity plan using an educational game. and a mathematical skill assessment form for preschool children Statistics used to analyze data Including the average percentage standard deviation The results showed that of preschool children, kindergarten 1, before and after organizing educational game activities The average score was 3.76 points and 8.32 points, respectively. And when comparing the scores before and after the educational game activities, it was found that the scores after the educational game activities were higher than before the educational game activities. Statistically significant at the 0.05 level.